Metode Endorphin Massage Dalam Menurunkan Kecemasan Pada Ibu Hamil Trimester III Di TPMB Linda Verawati Depok - Ekayanti; Saidah , Najmi Jihan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Anxiety is worried about something uncertain, excessive anxiety forms cortisol hormone which is not good for the fetus or the mother herself. (Maesaroh et al., 2020). Nearly 14% of sad pregnant women thought about hurting themselves. Meanwhile, in countries with high beliefs, 3% to 33% of pregnant women have suicidal thoughts. (Chauhan & Potdar, 2022). Endorphin massage is a non-pharmacological method of touch or massage given to pregnant women to be able to stimulate the body for relaxation or reduction of anxiety. (Wahidayanti & Suwanti, 2022). The purpose of this study was to determine the endorphin massage method in reducing anxiety in TM III pregnant women at TPMB Linda Verawati Depok . Methods: pre-experiment One-group pretest-posttest approach. Instruments used HARS scale (Hamilton Anxiety Rating Scale), using paired samples t-test test. The sample in this study were 3 trimester pregnant women (36-40 weeks) at TPMB Linda Verawati Depok 24 pregnant women. Results: of the study before the Endorphin Massage Method Intervention most of the mild anxiety and moderate anxiety were 11 pregnant women (45.8%). And after the Endorphin Massage Method Intervention, most of them were not anxious there were 9 pregnant women (37.5%) and mild anxiety 13 pregnant women (54.2%). Conclusion: of this study is that there is a decrease with the Endorphin Massage method with a p value of 0.000 where p is 0.05. It is recommended that the Endorphin Massage method can be an alternative choice for resolving anxiety in pregnant women in Trimester III